2015
DOI: 10.1002/mrc.4187
|View full text |Cite
|
Sign up to set email alerts
|

NMR metabolomics for soil analysis provide complementary, orthogonal data to MIR and traditional soil chemistry approaches – a land use study

Abstract: The present study was designed to analyse soils by different methodologies to determine the range of traits that could be investigated for the study of environmental soil samples. Proton nuclear magnetic resonance spectroscopy ((1) H NMR) was employed for metametabolomic analysis of soils from agricultural systems (managed) or from soils in a native state (remnant). The metabolomic methodologies employed (grinding and extraction with sonication) are capable of breaking up cell walls and so enabled characterisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…PCA demonstrated that the extracts from the composts and peat clustered in a manner that was correlated with their ability to suppress Phytophthora root rot. Similarly, Rochford et al [ 60 ] observed that growth inhibition against Bacillus subtilis of different soil extracts was strongly correlated with their metabolic profile. Metabolite composition is governed by the extant microbial communities in the substrate and it is well-known that pathogen inhibition may be mediated by the secretion of antibiotics or antimicrobial compounds [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…PCA demonstrated that the extracts from the composts and peat clustered in a manner that was correlated with their ability to suppress Phytophthora root rot. Similarly, Rochford et al [ 60 ] observed that growth inhibition against Bacillus subtilis of different soil extracts was strongly correlated with their metabolic profile. Metabolite composition is governed by the extant microbial communities in the substrate and it is well-known that pathogen inhibition may be mediated by the secretion of antibiotics or antimicrobial compounds [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 96%
“…The metabolic approach employed here was based on water extraction followed by data acquisition by liquid chromatrography-mass spectrophotometry-HPLC-MS; although it proved to be very effective in highlighting the diversity of compost microbiome, results cannot be directly compared with previous studies, where different extraction methods were used [ 60 , 71 ]. Results we obtained are to be considered preliminary and the involvement of metabolites in the ability of composts to suppress P .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other metabolomic studies, using techniques such as diffuse mid-infrared spectroscopy (Rochfort, Ezernieks, Kitching, & Mele, 2015) or direct infusion Fourier transform ion cyclotron resonance spectrometry (Llewellyn, Sommer, Dupont, Allen, & Viant, 2015) observed lipids to best differentiate location/habitat, whereas land use could not be separated.…”
Section: Can Cllp Assign Environmental Differences Related To Foresmentioning
confidence: 92%
“…A unique biomarker, macrocarpal was detected for Rhizoctonia solani-suppressive soil [195]. Similarly, NMR-based soil metabolic profiling was done to discriminate the suppressive and non-suppressive soils for disease resistance [196].…”
Section: Soil Metabolomicsmentioning
confidence: 99%